Mixed biosorbent of agro waste and bacterial biomass for the separation of Pb(II) ions from water system. (August 2021) - Saravanan, A.; Kumar, P. Senthil; Yaashikaa, P.R.; Karishma, S.; Jeevanantham, S.; Swetha, S.
Abstract: Adsorption of Pb(II) ions in aqueous systems by newly developed mixed biomass has been explored. Mixed biomass was prepared from agro-waste (raw Banyan tree bark, RBTB) and bacterial biomass ( Pannonibacter phragmitetus ). Chemical modification by sulphuric acid treatment of raw banyan tree bark (SMBTB) was accomplished for the effective separation of toxic Pb(II) ions from the aquatic system. FTIR, SEM and EDX analysis was utilized to deduce sorption characteristics of mixed biomass. Pb(II) ions maximal removal has occurred at pH-6.0, lead (II) ions concentration-25 mg/L, time and mixed biomass dosage (60 min and 3.5 g/L for RBTB – Pannonibacter phragmitetus ; 30 min and 1.5 g/L for SMBTB – Pannonibacter phragmitetus ) and temperature (30 °C). Data from equilibrium isotherm and kinetic analysis was best suited to the Langmuir model and pseudo-first-order kinetics. The spontaneous and exothermic nature of Pb(II) ions removal was described by thermodynamic parameters. The mixed biomass proved to be an effective and potential mixed biosorbent for toxic lead removal from solutions. Highlights: Agro waste biomass showed that low cost and effective adsorbent. Sulphuric acid modification enhances the adsorption capacity. Langmuir isotherm and Pseudo-first-order kinetics showed better fit. Adsorption of Pb(II) ion was spontaneous and thermodynamically exothermic.